Capital structure and energy firms performance in Malaysia - Ramlan H.; Mohd Saad N.; Mohamad N.E.; Haniff M.N. (Science and Engineering Research Support Society, 2023)
The objective of the study is to scrutinize an association between capital structure and energy firms performance in Malaysia. The data collected and retrieved from the energy company cover from period of 2005 to 2017 which are gathered from www.bursamalaysia.com, Bloomberg and Thomson Data Stream. Throughout, this study uses multivariate regressions to run the entire dependent variables for energy firms performance with its independent variables. In overall, the results are show that there are a statistically significant relationship between the capital structure and energy firms performance. 2019 SERSC.